Statin as a Combined Therapy for Advanced-Stage Ovarian Cancer: A Propensity Score Matched Analysis. (16th November 2016) - Chen, Hong-Yu; Wang, Qian; Xu, Qiu-Hong; Yan, Li; Gao, Xue-Feng; Lu, Yan-Hong; Wang, Li
Abstract : Background . Despite the great achievements in the treatment of advanced-stage ovarian cancer, it is still a severe condition with an unfavorable 5-year survival rate. Statins have been suggested to reduce the risk of several cancers beyond their cholesterol-lowing effects. However, the prognostic significance of statins in patients with advanced-stage ovarian cancer remains controversial. Methods . A retrospective study was performed to evaluate the association between statin intake and overall survival (OS) among patients with advanced-stage ovarian cancer. Patients who underwent cytoreductive surgery followed by courses of intravenous chemotherapy were matched through a propensity score analysis. Results . A total of 60 propensity-matched patients were included. Women in statin group showed a similar OS than the nonstatin counterparts (P = 0.966 ), whereas residual tumor was significantly associated with better OS (P = 0.013 ) and was an independent factor that associated with OS (P = 0.002, hazard ratio = 5.460, and 95% confidence interval: 1.894 to 15.742) in multivariable analysis. Conclusions . Our results suggested that statin usage was not associated with improved OS in patients with advanced-stage ovarian cancer undergoing surgery and chemotherapy. Considering the retrospective nature and the relative small sample size of the study, further prospective studies and random control trials are needed.